2011
DOI: 10.1111/j.1365-263x.2011.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines during the initial phase of oral mucositis in patients with acute lymphoblastic leukaemia

Abstract: It would seem that 96 h is an ideal time for determining the parameters evaluated both in blood and in saliva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 9 publications
0
37
1
1
Order By: Relevance
“…It has been reported in several human studies that the levels of pro-inflammatory cytokines are increased in the blood and saliva of patients during cancer treatment (14)(15)(16). Other studies using animal models have shown evidence of changes in the serum level and tissue expression of nuclear factor κ-B and the pro-inflammatory cytokines [TNF-α, interleukin (IL)-1β and IL-6) following administration of chemotherapeutic drugs (14,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported in several human studies that the levels of pro-inflammatory cytokines are increased in the blood and saliva of patients during cancer treatment (14)(15)(16). Other studies using animal models have shown evidence of changes in the serum level and tissue expression of nuclear factor κ-B and the pro-inflammatory cytokines [TNF-α, interleukin (IL)-1β and IL-6) following administration of chemotherapeutic drugs (14,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 97%
“…The reason why may be attributed to the subjects' systemic conditions and the chemotherapeutic agent, which was delivered every 2 days to the ALL children during the induction phase. High doses of methotrexate, which is used as a chemotherapeutic agent to kill leukemic cells, can damage the gingival tissues severely [9]. A previous study conducted by Morales-Rojas et al showed that administration of methotrexate after 96 h increased cytokine levels, including TNF-α [9].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this is the use of methotrexate, which is one of the most destructive chemotherapeutic agents [9]. Previous studies showed that high doses of methotrexate during the induction phase may lead to an increase of TNF-α levels in the oral cavity, which causes a severe pathological condition of the gingival tissue [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations